In vitro Antibacterial Efficacy of Non-Antibiotic Growth Promoters in Poultry Industry - Mashael R. Aljumaah; Manal M. Alkhulaifi; Alaeldein M. Abudabos (The Journal of Poultry Science, 2020)
Antibiotic growth promoters (AGPs) have been used for many years as supplements in various livestock diets, including those for poultry. However, the use of AGPs in feed was also associated with an increasing number of antibiotic-resistant bacteria in livestock. In this study, the in vitro antibacterial efficacies of eight commercially available non-AGPs suitable for use in poultry were investigated. Assessments included a combination of antibacterial activity assays and estimations of the minimal inhibitory and bactericidal concentrations along with scanning electron microscopy analysis. The results showed that the probiotic, CloStat® exerted a bacteriostatic effect against all tested bacteria, namely Salmonella Typhimurium, Escherichia coli, Staphylococcus aureus, and Clostridium perfringens, whereas Gallipro Tect® and Bacillus Blend® demonstrated bacteriostatic activity towards most of the pathogens tested. Other commercial non-AGPs, Sangrovit®, Fysal®, and Mix oil blend® showed a stronger or equal antibacterial activity compared to the positive control (AGP Maxus® G100) againsts all bacteria tested, except C. perfringens. Nor-Spice AB® and Varium™ did not show any significant effect against the tested bacteria. Several of the tested AGP substitutes exhibited good antibacterial efficiency against pathogenic bacteria and thus may be good candidates for second-stage in vivo investigations into reducing pathogen colonization in broilers.